DNA methylation program in developing hippocampus and its alteration by alcohol. - Yuanyuan Chen; Nail Can Ozturk; Feng C Zhou (PLoS ONE, 2013)
During hippocampal development, the Cornus Ammonis (CA) and the dentate gyrus (DG) undergo waves of neurogenesis and neuronal migration and maturation independently. This stage is widely known to be vulnerable to environmental stresses, but its underlying mechanism is unclear. Alcohol exposure has been shown to alter the expression of genes that regulate the fate, survival, migration and differentiation of pyramidal and granule cells. Undermining this process might compromise hippocampal development underlying the learning and memory deficits known in Fetal Alcohol Spectrum Disorders (FASD). We have previously demonstrated that DNA methylation was programmed along with neural tube development. Here, we demonstrated that DNA methylation program (DMP) proceeded along with hippocampal neuronal differentiation and maturation, and how this DMP was affected by fetal alcohol exposure. C57BL/6 mice were treated with 4% v/v ethanol through a liquid diet along with pair-fed and chow-fed controls from gestation day (E) 7 to E16. We found that a characteristic DMP, including 5-methylcytidine (5mC), 5-hydroxylmethylcytidine (5hmC) and their binding proteins, led the hippocampal neuronal differentiation and maturation spatiotemporally as indicated by their phenotypic marks in the CA and DG pre- and post-natally. Alcohol hindered the acquisition and progression of methylation marks, and altered the chromatin translocation of these marks in the nucleus, which was correlated with developmental retardation.